Implementation of Hotspot-PPPoE Network Monitoring and Security System Based on Mikrotik at FTIK UMKO - Fery Winata; Adi Wibowo (International Journal of Health Engineering and Technology, 2025)
The need for reliable and secure Internet connectivity in academic environments has become increasingly crucial to support the teaching and learning process. However, the wireless network (hotspot) at the Faculty of Engineering and Computer Science, University of Muhammadiyah Kotabumi, faces challenges in monitoring bandwidth usage and ensuring protection against unauthorized access. This study aims to design and implement an integrated network system capable of enhancing monitoring functions and security. The methodology employed is the Network Development Life Cycle (NDLC), which consists of the stages of analysis, design, implementation, and testing.The proposed system integrates user authentication through Hotspot and PPPoE (Point-to-Point Protocol over Ethernet), real-time traffic monitoring using MikroTik Hotspot Monitor, and improved router security through the Port Knocking technique. The implementation results demonstrate that the system is capable of providing centralized data on active users, bandwidth utilization, and activity logs. In addition, the application of Port Knocking successfully conceals critical service ports (Winbox, SSH) from external scans, allowing access only to administrators after performing the correct port-knocking sequence. Overall, this system significantly enhances monitoring capabilities and strengthens the security of the network infrastructure within the faculty environment.